Impact of dialect use on a basic component of learning to read - Brown, Megan C.; Sibley, Daragh E.; Washington, Julie A.; Rogers, Timothy T.; Edwards, Jan R.; MacDonald, Maryellen C.; Seidenberg, Mark S. (Frontiers in Psychology, 2015)
Can some black-white differences in reading achievement be traced to differences in language background? Many African American children speak a dialect that differs from the mainstream dialect emphasized in school. We examined how use of alternative dialects affects decoding, an important component of early reading and marker of reading development. Behavioral data show that use of the alternative pronunciations of words in different dialects affects reading aloud in developing readers, with larger effects for children who use more African American English. Mechanisms underlying this effect were explored with a computational model, investigating factors affecting reading acquisition. The results indicate that the achievement gap may be due in part to differences in task complexity: children whose home and school dialects differ are at greater risk for reading difficulties because tasks such as learning to decode are more complex for them.